1994
DOI: 10.1159/000236769
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Recovery following Chronic Treatment with Compound 48/80

Abstract: Histochemical and functional properties of mast cells (MC) in Brown Norway rats recovering from chronic treatment with the MC secretagogue compound 48/ 80 were examined. In the skin, treatment for 5 days with compound 48/80 resulted in a marked decrease in MC subpopulations defined by differential alcian blue/safranin staining. Both safranin-positive connective tissue MC and alcian blue staining MC were reduced in number. This was accompanied by significant decreases in skin histamine and rat MC serine proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…We observed a significant decrease in toluidine blue-positive MH mast cell number in C48/80 treated birds, as previously reported in mammalian and avian species (Ibrahim, 1970;Jaffery et al, 1994;Ribatti et al, 1992). This was expected because upon C48 /80 treatment, mast cells lose their granular material and the glycosaminoglycans contained therein.…”
Section: Degranulation Of Mast Cells By C48/80supporting
confidence: 90%
“…We observed a significant decrease in toluidine blue-positive MH mast cell number in C48/80 treated birds, as previously reported in mammalian and avian species (Ibrahim, 1970;Jaffery et al, 1994;Ribatti et al, 1992). This was expected because upon C48 /80 treatment, mast cells lose their granular material and the glycosaminoglycans contained therein.…”
Section: Degranulation Of Mast Cells By C48/80supporting
confidence: 90%
“…Chronic treatment with C48/80 has been shown to deplete mast cells of their granular contents (Jaffery et al, 1994;Karadag et al, 2000). Adenosine is involved in asthma through its ability to promote or enhance mediator release from mast cells (Peachell et al, 1988;Jacobson and Bai, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Jaffery et al (1994) reported that the number of mast cells in skin decreased by chronic treatment with compound 48/80 by differential alcian blue/safranin staining. There is a possibility that the mast cells cannot be detected by alcian blue because of the complete degranulation by compound 48/80.…”
Section: Discussionmentioning
confidence: 99%